Binding of vitronectin and Factor H to Hic contributes to immune evasion of Streptococcus pneumoniae serotype 3 - Kohler, Sylvia; Hallström, Teresia; Singh, Birendra; Riesbeck, Kristian; Spartà, Giuseppina; Zipfel, Peter F.; Hammerschmidt, Sven (Thrombosis and Haemostasis, 2015)
Streptococcus pneumoniae serotype 3 strains are highly resistant to opsonophagocytosis due to recruitment of the complement inhibitor Factor H via Hic, a member of the pneumococcal surface protein C (PspC) family. In this study, we demonstrated that Hic also interacts with vitronectin, a fluid-phase regulator involved in haemostasis, angiogenesis, and the terminal complement cascade as well as a component of the extracellular matrix. Blocking of Hic by specific antiserum or genetic deletion significantly reduced pneumococcal binding to soluble and immobilised vitronectin and to Factor H, respectively. In parallel, ectopic expression of Hic on the surface of Lactococcus lactis conferred binding to soluble and immobilised vitronectin as well as Factor H. Molecular analyses with truncated Hic fragments narrowed down the vitronectin-binding site to the central core of Hic (aa 151–201). This vitronectin-binding region is separate from that of Factor H, which binds to the N-terminus of Hic (aa 38–92). Binding of pneumococcal Hic was localised to the C-terminal heparin-binding domain (HBD3) of vitronectin. However, an N-terminal region to HBD3 was further involved in Hic-binding to immobilised vitronectin. Finally, vitronectin bound to Hic was functionally active and inhibited formation of the terminal complement complex. In conclusion, Hic interacts with vitronectin and simultaneously with Factor H, and both human proteins may contribute to colonisation and invasive disease caused by serotype 3 pneumococci.
Keywords: Complement; Hic; pathogenesis; PspC11; serotype 3; Streptococcus pneumoniae; vitronectin